2022
DOI: 10.1002/ijgo.14515
|View full text |Cite
|
Sign up to set email alerts
|

Climate change vulnerability, and health of women and children: Evidence from India using district level data

Abstract: Objective To understand how climate change vulnerability is associated with women and children's health (WCH) at the district level in India. Methods The district‐specific climate change vulnerability index was mapped to the district level NFHS‐5 data (N = 674). Fractional regression and spatial analyses were performed to examine the strength of association and the presence of geographic clustering. Results Bivariate analysis revealed that the levels of WCH indicators were lower in districts with a high vulner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…Research on the impact of climate change on the region’s severe rainfalls has shown that these events are non-stationarous (Yilmaz 2015 ; Yilmaz 2017 ). Understanding local climate vulnerabilities is crucial because of the influence of climate change on a variety of factors, including agricultural pests (Kutywayo et al 2013 ), erosion and land cover changes (Coşgun 2017 ), and health consequences (Mahapatra et al 2022 ). These effects have been examined in numerous districts worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the impact of climate change on the region’s severe rainfalls has shown that these events are non-stationarous (Yilmaz 2015 ; Yilmaz 2017 ). Understanding local climate vulnerabilities is crucial because of the influence of climate change on a variety of factors, including agricultural pests (Kutywayo et al 2013 ), erosion and land cover changes (Coşgun 2017 ), and health consequences (Mahapatra et al 2022 ). These effects have been examined in numerous districts worldwide.…”
Section: Introductionmentioning
confidence: 99%